A Comparison of Liability Between Partners in a Civil Partnership and Partners in a Firm - Sharfina, Nurul Hulwanita (Alauddin Law Development Journal (ALDEV), 2024)
The research aims to examine the distinctions in liability between partners in civil partnerships and those in firms, while exploring the legal implications of the partnership establishment from the Civil Code perspective. The research was a normative juridical approach with legislative and used the qualitative analysis. The research found that the necessity for civil partnerships to adhere to the guidelines outlined in Regulation No. 17 of 2018. While aligning a civil partnership's name with Regulation No. 17 of 2018 does not alter partners' liability towards third parties to mimic that of firm partners, it highlights the unique management and liability characteristics distinguishing civil partnerships from firms. Consequently, there exist discrepancies in partner liability towards third parties: in civil partnerships, liability pertains solely to members involved in legal actions and is personal, whereas in firms, liability is shared among all partners.